STUDI FENOMENOLOGI AKUNTABILITAS SBSQUAD ENTERTAINMENT SEBAGAI INDUSTRI KREATIF - Febrayana Maryushanti Wijawa (Jurnal Akuntansi Aktual, 2017)
The purpose of this study is understanding the accountability and financial management of a community in creative industry field that operated without profit orientation. This study uses phenomenology approach. The subject of this study is SBSquad Entertainment. The results of this study are (1) SBSquad Entertainment is a community in creative industry field with a simple financial management and have no profit orientation; (2) The closeness factor between members with management and steering committee add the members’ trust towards them that cause the absence of formal accountability necessities.Keywords:Accountability, creative industry, phenomenology